Impact of α‐amylase supplementation on energy balance and performance of high‐yielding dairy cows on moderate starch feeding. (30th October 2017) - Bachmann, Martin; Bochnia, Mandy; Mielenz, Norbert; Spilke, Joachim; Souffrant, Wolfgang B.; Azem, Elisabeth; Schliffka, Wolfgang; Zeyner, Annette
Abstract: In dairy cows, exogenous α‐amylase is suggested to improve starch utilization and positively affect performance and health traits linked to energy balance and fertility. In a 1‐year feeding experiment, 421 cows were orally supplemented with α‐amylase (treatment: 12.5 g/kg dry matter (DM) addition rate to a concentrated feed) or non‐supplemented (control) on the basis of an ad libitum total mixed ration (TMR). Every cow was allocated to a high‐ (≥32 kg milk/day) or late‐lactation group (<32 kg milk/day), in which the TMR starch content was 220 ± 20.8 g/kg DM and 183 ± 24.8 g/kg DM, respectively. The energetic effect of α‐amylase supplementation seemed to be exclusively related to the high‐lactation stage (5–100 days in milk) in primiparous cows, where the daily milk yield was 32 ± 0.49 versus 31 ± 0.50 kg per cow in the treatment versus control group ( P  <   0.05). The pluriparous cows did not benefit from the supplementation that way. In neither primiparous nor pluriparous cows, was the milk composition, the fat‐to‐protein ratio, the somatic cell score, the backfat thickness, serum total bilirubin, β‐hydroxybutyrate and the fertility found to be systematically affected by α‐amylase supplementation.